Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.3 Product and Quotient Rules - Exercises: 19

Answer

$f’(3) = -\frac{1}{169} $

Work Step by Step

$f(x) = \frac{1}{x+10} = (x+10) ^{-1}$ Power Rule: $f’(x) = -1(x+10)^{-2} $ $f’(x) = -\frac{1}{(x+10)^2} $ Evaluate f’(x) at x=3: $f’(3) = -\frac{1}{(3+10)^2} = -\frac{1}{(13)^2} $ $f’(3) = -\frac{1}{169} $
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.